International Diversification Benefits In Asean Stock Markets: A Revisit - Lim, Kian-Ping; Lee, Hock-Ann; Liew, Venus Khim-Sen (Universiti Putra Malaysia, 2003)
With abounding evidence supporting the presence of non-linearity in stock returns series, coupled with theoretical and empirical works suggesting a potential loss in standard Johansen cointegration method if the underlying data generating process is non-linear in nature, this study re-examines the issue of stock markets integration in the ASEAN region using a more robust test. Specifically, the Bierens’s (1997) non-parametric cointegration test is selected in views of its potential superiority over standard linear Johansen and Juselius (1990) method at detecting cointegration when the data generating process is non-linear. The results from the Bierens’s test indicate that there is a common force which brings all the five ASEAN stock markets together in the long run. In this case, the shocks from any of these five markets may spillover to the other markets in the same region. The recent Asian financial crisis bears a good testimony to this ‘contagion effect’. More importantly, the Bierens’s (1997) nonparametric cointegration test provides robust evidence suggesting that there would be no long run gain from international portfolio diversification. Specifically, investors with long run horizons may not benefit from an investment made across the countries in this ASEAN region. One possible explanation for this intra-ASEAN stock markets integration is their strong economic ties, especially intra-ASEAN trade and investment that has indirectly linked their stock indices.